Comparing Fuzzy rule-based and fractional Open Circuit Voltage MPPT techniques in a fuel cell stack - N. Luta, Doudou; K. Raji, Atanda (International Journal of Engineering and Technology, 2019)
The concept of power tracking was at first applied to renewable power systems and especially those based on solar and wind to extract as much power as possible from them. Both types of power systems operate on the principle of converting either solar or wind into electricity. Thus, their output power is direct dependent on the solar radiation for solar power systems and on the wind speed for wind generators. To maintain efficient system operations, the output power of these power systems is optimized through maximum power tracking techniques. In the similar vein, fuel cell stacks display nonlinear output powers resulting from internal limitations and operating parameters such as tem-perature, hydrogen and oxygen partial pressures and humidity levels, etc., leading to a reduced system performance. It is critical to extract as much power as possible from the stack, thus, to prevent also an excessive fuel use. To ensure that, the power converter interfaced to the stack must be able to self-adjust its parameters continuously, hence modifying its voltage and current depending upon the maximum power point position. Diverse techniques are utilized to extract maximum power from the fuel-cell stack.Â  In this paper, a fractional open circuit voltage and fuzzy rule based maximum power tracking techniques are considered and compared. The proposed system consists of a 50 kW Proton Exchange Membrane fuel cell interfaced to a DC-to-DC boost converter. The converter is designed to deliver 1.2 kV from 625 V input voltage. The simulation is carried out under Matlab/Simulink environment.Â Â
Keywords: Use about five key words or phrases in alphabetical order; Separated by Semicolon.